ANTIMICROBIAL ACTIVITY OF EXTRACTS OF ADENANTHERA PAVONINA AND MUSSAENDA PHILIPPICA AGAINST ISOLATED BACTERIA AND FUNGI.: Life Sciences-Microbiology - RENILDA SOPHY A.J; ALBIN T. FLEMING; B.S.M. RONALD; K. GOWRI SHANKAR; R. VIDHYA; V. RAJAGOPALAN; A. SHEEBA; R DURGALAKSHMI (International Journal of Life Science and Pharma Research, 2022)
Long before mankind discovered the existence of microbes, the idea of using certain plants for medicinal purpose because of their healing potential due to antimicrobial principles, was well accepted. In the past few decades, the search for new anti-infection agents has occupied many research groups in the field of ethnopharmacology. In the present paper, we analyze two medicinal plants, both as potential antimicrobial crude drugs as well as a source for natural compounds that can act as new anti-infection agents. The antibacterial and antifungal activity of three solvent extracts of Adenanthera pavonina and Mussaenda philippica on microbes isolated from dairy cattle rearing unit was studied. The results revealed that these extracts have antibacterial activity against Salmonella enteritidis, Klebsiella pneumoniae, Bacillus subtilis, Staphylococcus aureus, Escherichia coli and Pseudomonas aeruginosa and hence these crude extracts can be used as anti-infection agents in dairy cattle rearing unit to avoid infections especially to calves which are prone to infections at birth.